Accelerated Pension Fund Calculations Using the Individual Level Premium Method and the Projected Unit Credit Method Case Study: PT. Dirgantara Indonesia - Rohman, Aletta Divna Valensia; Mayaningtyas, Chibi Adinda (iora, 2024)
This paper examines the calculation of accelerated pension funds using two actuarial methods: the Individual Level Premium (ILP) method and the Projected Unit Credit (PUC) method. The case study focuses on PT. Dirgantara Indonesia. We compare the methods' impact on normal contribution amounts, actuarial liabilities, and retirement benefits. The research highlights the advantages and disadvantages of each approach, considering factors like participant age and contribution period. The findings demonstrate that the PUC method generally leads to lower normal contributions but may result in lower final retirement benefits compared to the ILP method. This study provides valuable insights for companies and employees in PT. Dirgantara Indonesia to choose the most suitable method for their accelerated pension plan, considering their financial goals and risk tolerance.